Coke and sintering resistant nickel atomically doped with ceria nanosheets for highly efficient solar driven hydrogen production from bioethanol. Issue 5 (8th February 2022) - Yuan, Dachao; Peng, Yahang; Ma, Luping; Li, Jianchang; Zhao, Jianguo; Hao, Jianjun; Wang, Shufang; Liang, Baolai; Ye, Jinhua; Li, Yaguang
Abstract : Ni single atoms doped with CeO2 nanosheets combined with a Ti2 O3 based photothermal device showed 3 Suns driven ESR with 462 °C temperature, 519 mmol g −1 h −1 H2 production rate, 16.7% solar-to-fuel efficiency and 60 hours of stable operation. Abstract : Using bioethanol steam reforming (ESR) to produce green hydrogen is restricted by the low activity, coke, sintering of Ni-based catalysts as well as the consumption of fossil energy, which all have not been addressed. Here, a new strategy of doping Ni single atoms in CeO2 nanosheets (Ni SA/CeO2 ) is able to make the catalysts highly active and stable for ESR due to the unexpected coke and sintering resistance. Theoretical studies reveal that Ni SA/CeO2 can not only reduce the reaction barrier of ethanol decomposition and water decomposition to improve the ESR activity but also change the intermediates and enhance the metal–support interaction to avoid the coking and sintering due to stabilization of oxidized Ni 2+ species. Furthermore, the 3 Suns illuminated temperature of Ni SA/CeO2 can be increased from 115 °C to 462 °C using a novel Ti2 O3 photothermal device due to the synergy of efficient solar absorption and low thermal radiation, which results in 519 mmol g −1 h −1 ESR H2 production rate, 16.7% solar-to-fuel efficiency and 60 h of stable operation, superior to the existing sunlight driven ethanol dehydrogenation systems. This study opens a novel route to solar driven green hydrogen production capable for industrial application.